2015
DOI: 10.1016/j.jstrokecerebrovasdis.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dysphagia, National Institutes of Health Stroke Scale Score, and Predictors of Pneumonia after Ischemic Stroke

Abstract: There was no relation between the NIHSS score and laryngeal penetration or laryngotracheal aspiration, and the principal predictors of pneumonia in dysphagic patients after ischemic stroke were advanced age and neurologic severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 37 publications
2
19
1
1
Order By: Relevance
“…In line with this reasoning, lower NIH-SS cutoff values for infratentorial strokes triggering an instrumental swallowing assessment were found in our study. The fact that the NIH-SS shows less sensitivity for items involving the vertebral-basilar system may also explain why Ribeiro et al [19], unlike our results, found no significant relation between laryngeal penetration or aspiration and the NIH-SS in a mixed stroke population in an earlier study.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In line with this reasoning, lower NIH-SS cutoff values for infratentorial strokes triggering an instrumental swallowing assessment were found in our study. The fact that the NIH-SS shows less sensitivity for items involving the vertebral-basilar system may also explain why Ribeiro et al [19], unlike our results, found no significant relation between laryngeal penetration or aspiration and the NIH-SS in a mixed stroke population in an earlier study.…”
Section: Discussioncontrasting
confidence: 93%
“…Few studies have addressed the role of the NIH-SS as a predictor for PSD [14][15][16][17][18][19] with inconclusive results due to variability in study design and patient selection, for example, in 1 study dysphagia was only found in supratentorial stroke patients [16]. A further limitation has been that diagnostic criteria for dysphagia in these studies were substantially variable and only few used instrumental assessment, that is, VFS [14].…”
Section: Introductionmentioning
confidence: 99%
“…Age [1718], black race [18], initial GCS score [18], ICH volume [1819] and Functional Independence Measure (FIM) scores on admission [17] were known to be independent predictors for long-term dysphagia in patients with hemorrhagic stroke. In comparison, the NIHSS score [2021], age [202122], left-sided lesion [23], history of diabetes [22], and baseline functional independence [21] were risk factors for dysphagia in ischemic stroke. The GCS is the one of the important prognostic factors for functional recovery in aSAH [24]: the poor neurological status at the onset as captured by the GCS and NIHSS affected the prognosis of dysphagia in both ischemic and hemorrhagic strokes as a result.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case series reported by Pikus and colleagues lends credence to the idea that divisions of airway invasion by depth (i.e., PAS level 1 vs levels 2–5, levels 6–7 and level 8) are associated with relative risk for pneumonia [ 23 ]. However, other studies suggest that the relationship is not that straight forward [ 25 ]. It is well accepted in clinical circles that not every patient with tracheobronchial aspiration (whether sensate or silent) will progress to developing pneumonia [ 24 , 26 ].…”
Section: Construct Validitymentioning
confidence: 99%